ANALISA MOTIVASI KERJA TERHADAP KINERJA KARYAWAN EXPERIENCE DENTAL CARE BALIKPAPAN - Patria Rahmawaty; Dessy Handa Sari; Nurul Musfirah Khairiyah (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Motivation is an impulse that comes from within the individual that directs to do something. Motivation also affects the quality of performance of employees. The purpose of this study was to determine the level of work motivation of Experience Dental Care Balikpapan employees and to find out how to increase the work motivation of Experience Dental Care Balikpapan employees on their performance. This study uses a qualitative method. descriptive The research was conducted for 8 months and took place at Experience Dental Care Balikpapan which is part of the clinic at Siloam Hospitals Balikpapan. The results of this study indicate that the work motivation of 4 employees is in the fairly high/ high category; still standard / not needed repair. Meanwhile, 6 people are included in the Very High category, which means that the employee needs to get special treatment from the company leadership. To increase work motivation, it can be done by applying a reward system as a form of appreciation for employee performance and this has been done by the leader of Experience Dental Care.